2022
DOI: 10.1057/s41282-022-00302-3
|View full text |Cite
|
Sign up to set email alerts
|

Emotional cycles and collective action: Global crises and the World Social Forum

Abstract: As the world suffers the effects of the Covid-19 pandemic, global justice activists pursue political solutions to its devastating consequences especially on the weakest sections of the world’s population. I analyse activists’ responses to the 2008 financial crisis to reflect on how collective action is impacted by social crises. The global justice movement and the financial sector face recurring, intertwined, and inversely related cycles of exuberance and crash. I find that, on the one hand, the prevalence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Empirical evidence has shown that discontent is necessary, but not sufficient to explain participation in social movements (Cárdenas and Blanco, 2006). Current evidence suggests that emotions play a determining role in action within these contexts (Jasper, 2011;Poma and Gravante, 2017;Van Ness and Summers-Effler, 2018;Curnow and Vea, 2020;Caruso, 2022). These actions are expressed in different forms of political participation, in which emotions can increase participation, fostering anger and fear, which are related to political discontent and increase the probability of involvement (Valentino et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence has shown that discontent is necessary, but not sufficient to explain participation in social movements (Cárdenas and Blanco, 2006). Current evidence suggests that emotions play a determining role in action within these contexts (Jasper, 2011;Poma and Gravante, 2017;Van Ness and Summers-Effler, 2018;Curnow and Vea, 2020;Caruso, 2022). These actions are expressed in different forms of political participation, in which emotions can increase participation, fostering anger and fear, which are related to political discontent and increase the probability of involvement (Valentino et al, 2011).…”
Section: Introductionmentioning
confidence: 99%